STUDENTS’ PERCEPTIONS IN USING NARROW READING AND NARROW LISTENING IN SPEAKING CLASS AT THIRD SEMESTER OF ENGLISH DEPARTMENT UNIVERSITAS BANDAR LAMPUNG - Rizky Adelia Putri; Yanuarius Yanu Dharmawan (Universitas Bandar Lampung, 2022)
This research describes the student’s perceptions in using narrow reading and narrow listening in speaking class at third semester of English Department Universitas Bandar Lampung. It is to find out the student’s perception about narrow reading and narrow listening whether those methods are effective or not to be used in speaking class, and whether those methods could help them in improving their speaking ability or not. The population of this research were the third semester students of English Department Universitas Bandar Lampung. The sample of this research was taken by using purposive sampling method. The instruments used for collecting the data were observation, questionnaire, and interview. The data analysis of this research was qualitative. The result of this research show that the students were very interested in learning and they gave a positive attitude and good response when those methods were implemented in their classes. From the questionnaire and the interview result, it shows that mostly they said that those methods can help them to speak as well as to understand what they should say when they should tell their topic in front of the class. Based on the research, it was found that the use of narrow reading and narrow listening in speaking class was effective and it was very useful and help the students in improving their speaking skill as well as help the students in achieving their goal in learning speaking skill. Therefore, it was suggested to use narrow reading and narrow as a media in teaching English generally and teaching speaking skill particularly.